The overlooked role of discourse in breaking carbon lock‐in: The case of the German energy transition. (10th January 2019) - Buschmann, Pia; Oels, Angela
Abstract : Over the last 15 years, research on carbon lock‐in has investigated why decarbonization evolves so slowly in Western industrialized countries. In this paper, we argue that the role of discourses has been overlooked in the literature on carbon lock‐in. We argue that discourses are both part of lock‐in mechanisms and, using the concept of discursive turning points, important factors in explaining change. This implies that we need to carefully investigate the dominant discourses that constitute and justify the very technologies, institutions and behaviors of the status quo. For the case of the German energy transition, we demonstrate the importance of discursive turning points for overcoming carbon lock‐in, based on a literature review. Germany's long‐standing lock‐in of fossil fuels and nuclear power was undermined by the rise of the energy transition discourse. This discourse transitioned from a very marginal position to dominance through a number of factors, winning against the energy mix discourse. Over time the energy transition discourse became de‐radicalized. Coal has been able to defend its role in the German energy mix in the name of affordability and energy security. While renewables continue to grow, this happens alongside a remaining carbon lock‐in. We conclude that discursive lock‐in and discursive turning points are useful analytical tools that help to explain how the transition to renewable energies unfolds. In future research, the interaction between discursive lock‐ins and other types of lock‐in should be investigated. This article is categorized under: The Carbon Economy and Climate Mitigation > Decarbonizing Energy and/or Reducing Demand Policy and Governance > Governing Climate Change in Communities, Cities, and Regions Abstract : Discursive turning points in the German energy transition.